Migration in the ABCD assessment tool after community-based pulmonary rehabilitation - Marques, A. (2022)
Objectives: The ABCD assessment tool (ABCD) proposed by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) is often used to guide treatment in chronic obstructive pulmonary disease (COPD). However, treatment remains focused on pulmonary pharmacology, despite being known that this will have minimal effects on meaningful aspects of people’s daily life such as symptoms. Pulmonary rehabilitation (PR), an evidence-based, multidisciplinary, non-pharmacological intervention, improves symptoms and may lead to a positive shift in the ABCD assessment tool but this remains underexplored. Hence, we aimed to assess the effects of a community-based PR programme on the ABCD assessment tool. Methods: An observational study with people with COPD was conducted. Age, sex, forced expiratory volume in one second percentage predicted (FEV1%predicted); activities-related dyspnoea-modified British Medical Research Council questionnaire (mMRC), impact of the disease-COPD Assessment Test (CAT) and number of acute exacerbations and hospitalisations in the previous year to determine participants’ group in the ABCD assessment tool were collected before and after a 12-weeks community-based PR programme. Paired samples t-test and Wilcoxon signed rank test were used to analyse data. Results: Eighty-nine people with COPD (69.5 ± 8.3 yrs; 78.7% male; FEV1 = 50.1 ± 17.8% predicted) were included. Airflow obstruction remained unchanged after PR (p = 0.908). In the ABCD assessment tool, the number of individuals allocated to GOLD A (CAT: 15 (16.9%) vs. 26 (29.2%); mMRC: 26 (29.2%) vs. 34 (38.2%)) and C (CAT: 1 (1.1%) vs. 6 (6.7%); mMRC: 4 (4.5%) vs. 11 (12.4%)) increased, whilst, those allocated to GOLD B (CAT: 51 (57.3%) vs. 40 (44.9%); mMRC: 40 (44.9%) vs. 32 (36%)) and D (CAT: 22 (24.7%) vs. 19 (21.3%); mMRC: 19 (21.3%) vs. 12 (13.5%)) decreased following PR, using either the CAT (p = 0.002) or the mMRC (p = 0.001) (Figure 1 - a) and b)). Conclusions: Community-based PR reduces symptoms in people with COPD, leading to positive and significant shifts in the ABCD assessment tool. Referrals to PR are strongly encouraged.